Ban Conversion Therapy in Asia: Digital Activism in ILGA Asia’s Transnational Advocacy Networks - Dewi, Putu Ratih Kumala; Simatupang, Zakharia Billy Aprilius; Abigail, Sarah; Variza, Baiq Nayla Adisty (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
Lesbian, Gay, Bisexual, Transgender, Queer, etc (LGBTQ+) issues are still debated in society. Until now, LGBTQ+ people face many obstacles in fighting for their rights. Movement space has become a polemic for LGBTQ+ people throughout the world. In some countries, healing therapy or called conversion therapy is even implemented. This is said to be a way that can cure LGBTQ+ people that aimed at changing people's sexual orientation or gender identity. However, in practice the therapy is conducted without regard for human safety, involving mental and physical torture. Therefore, conversion therapy must be abolished because of harmful and abusive practice. It has encouraged the emergence of social movements against conversion therapy in various countries, including Asia. Through this research, the author aims to analyze the strategy of the movement to eliminate conversion therapy in Asia carried out by ILGA Asia. This research uses a qualitative descriptive research method by collecting secondary data through online and printed literature. By using new social movement theory, transnational advocacy networks and the concept of digital activism, the author will analyze how ILGA Asia carries out social prohibition conversion therapy movements in Asia and the actors involved in each country, namely Bangladesh, India, Indonesia and Sri Lanka. Through this research, the author found that ILGA Asia uses digital activism through online petitions and videos on social media in carrying out its movement and involving local non- governmental organizations in each country.